PENGARUH MODAL DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Yahdillah; Itsnaini Chusnul Khotimah; Hairunnisa (Al-Iqtishad: Jurnal Ekonomi Syariah, 2024)
This study aims to analyze the effect of capital and operational efficiency on the profitability of Islamic banks in Indonesia. The data used in this study are secondary data obtained from Sharia Banking Statistics (SPS) at the Financial Services Authority (OJK) during the period 2020-2023. The research method used is quantitative research with multiple linear regression analysis. The results of the analysis show that capital has a significant effect which is worth 0.0050 <0.05, so Ha is accepted and operational efficiency has a significant effect worth 0.0076 <0.05, so Ha is accepted. Simultaneously CAR and BOPO affect ROA with a significant value of 0.000 <0.05. The implication of this research is the importance of increasing capital as one of the factors that can increase the profitability of Islamic banks in Indonesia.